Aspectos socioeconômicos e ocupações nos rincões dos Mendes e da Chirca - APA do rio Ibirapuitã/RS - Rozalino, Luciano (2013)
Within the historical process of formation of the territory Rio-Grandense, many social actors were hidden in the Pampa region. The almost ubiquitous presence of large pastoral property (Estância) just covering a wide social diversity, giving the false idea of homogeneous region. However, recent research has begun to identify important actors and have always been part of the mosaic pampiano, such as the "Pecuarista Familiar". But other actors remain poorly understood. The present study sought to contemplate the universe of rural populations called Rincões. Tried to highlight socioeconomic aspects and identify the occupations present in these rural communities. The Rincões are characterized by being small settlements in Pampa where people reside with small portions of land that survive the various occupations tied the estâncias and activities of beef cattle. The study focused on a portion of the municipality of Rosario do Sul , in the region of the Pampa biome within the Preservation Area River Environmental Ibirapuitã (APA Ibirapuitã). Were taken as reference for the case study two Rincões (Rincão of Mendes and the Rincão of Chirca). The Rincão of Mendes characterized by having small properties and very high population aged. Families have few animals and plants surrounded intended for consumption and eventual sale of animals (cattle). Pensions comprise the largest monetary entries in families, being responsible for the maintenance of the same. Pensions are from the former activities provided outside the property, in the nearby estânias. In Chirca, the population is younger most men are employed in positions related to livestock in the nearby estâncias. For women, staying household duties. The study also pointed to a high degree of satisfaction (in both Rincões reference) in relation to where they live, and to rural activities and occupations that play.